Modeling the influence of industry forces on intention to invest in renewable energy resources with the moderating effect of sustainable competitive strategy. Issue 1 (31st December 2022) - Appiah, Michael Karikari; Sedegah, Daniella Delali; Ayisi-Addo, Angela Kyerewaa; Kwaku Gyening, Emmanuel
Abstract: In response to Agenda 2030 and the Paris Climate Accord, the Ghana Energy Transition has been inaugurated to ensure a speedy shift from fossil fuel sources to clean energy (Solar, Wind, Thermal, Ocean Energy, Hydro Energy etc.) to avoid the worst of climate change. To facilitate the transition, we have developed an integrated model to explain the relationship between industry forces and investment intentions in renewable energy resources, and the moderating role of sustainable competitive strategy on the relationship between industry forces and investment intention. Cross-sectional survey data from Ghanaian private firms have been collected between January and February, 2022, and used for the study. To test our hypotheses, structural equation modelling approach and SMART-PLS 3.3.1 have been used. The results have shown that industry forces have significant effects on investment intention. The results have further shown that sustainable competitive strategy has significant relationships with investment intention. Moreover, the sustainable competitive strategy dimension of entrepreneurial competency has moderated the relationship between industry forces and investment intention. These results offer theoretical, policy and practical implications and guidance on strategies needed to attract private investment in renewable energy resources in Ghana and beyond.